Evaluación del ciclo vegetativo del hongo REISHI (GANODERMA LUCIDUM) con diferentes sustratos en el Cantón La Maná. - Gonzalez Vega, Ambar Stefania (2023)
Ganoderma lucidum also known as “reishi” or “lingzhi” is a medicinal mushroom that is called as the miraculous King of herbs. The reishi mushroom has the ability to maintain a healthy body and promote longevity, due to its medicinal properties like anti oxidant, anti tumor, and anti viral. In addition, millions of tons of agro-industrial waste are generated worldwide which are not used, on the contrary, a large amount is incinerated and taken to landfills where they cause environmental pollution. The present research was carried out in El Carmen parish that is located in La Maná canton, Cotopaxi province. In this research work the following objectives were proposed: To evaluate the vegetative cycle of the reishi mushroom (Ganoderma lucidum) with different substrates in La Maná canton. To determine the type of substrate that achieves vegetative development of the reishi mushroom (Ganoderma lucidum). To demonstrate the adaptation and production of the reishi mushrom (Ganoderma lucidum) in La Maná canton. To carry out the benefit/cost análisis of the studied substrates. According to this, a Completely Randomized Design (CRD) was used. The evaluated variables were: the percentage of colonization (%), days of emergence, number of fungi per pod, cap diameter (cm), days to harvest, fruiting body weight (g), and cost/benefit analysis. The best results for the studied variables were the percentage of mycelial colonization with values of 10%, 20%, 20%, 17%, 17%, 7%, in rice husk, days of primordium emergence from 5 to 20 days in barley straw and Mixture (ACP), number of fungi per pod with a value of 15 units in pygus sawdust followed by barley straw, cap diameter with an average of 8,03 cm, in barley straw, days to harvest on 75 days in barley straw and Mixture (ACP), average weight of fruiting body of 109 g in Mixture (ACP), and resulting in the bromatological analysis rice husk with 23.543% protein, 6.08% fat, 1.74% ash, 33,98% fiber as the best treatments, and with a positive benefit/cost of $0.40 from the Mix substrate (ACP).